Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Answer:
x=4
Step-by-step explanation:
(x-2)(x+1)=3x-2
x(x+1)-2(x+1)=3x-2
x^2+x-2x-2=3x-2
x^2-x-2=3x-2
x^2=3x+x-2+2
x^2=4x
x^2/x=4
x=4
(x - 2) ( x + 1) = 3x - 2
x² + x - 2x - 2 = 3x - 2
x² + x - 2x - 2 - 3x + 2 = 0
x² - 4x = 0
x ( x - 4 ) = 0
x - 4 = 0/x
x - 4 = 0
x = 4
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.